Implementation of maternal near-miss guidelines in the selected district and womens hospitals of Maharashtra, India - Kulkarni, Ragini N.; Deshpande, Aniruddha V.; Begum, Shahina; Shivkumar, Poonam V.; Patil, Anushree D.; Srimathi, G.; Patil, Archana V.; Chauhan , Sanjay L. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Effective implementation of operational guidelines depends on understanding the facilitating factors and barriers which are useful for scaling up the implementation at other facilities. The objective of the present study was to document the facilitating factors and barriers for implementation of the MNM‑R guidelines at the selected district and women’s hospitals in Maharashtra, India. Methods: The incidence and factors influencing MNM events in the selected hospitals were reviewed and delays based on three-delay model were identified during April 2018 to March 2022. All pregnant/post-partum women meeting eligibility criteria of MNM as per GOI guidelines were included as Near Miss cases (n=460) and interviewed. All the MNM cases were discussed during the monthly maternal death review (MDR) meetings at these hospitals. Results: Ratio of maternal deaths to MNM was 1:2.34. Leading causes of MNM were hemorrhage (64.6%) and hypertensive disorders of pregnancy (23.0%). Level one and two delays were reported by 41.7% and 7.6% women respectively. Level three delay at referral centers and at district hospitals was reported by 15.8% and 12.2% women respectively. Corrective measures were taken care of as per the gaps identified on the basis of three delay model for prevention of these cases in future. The study findings indicate facilitating factors and barriers which need to be addressed for effective implementation of MNM guidelines at the district hospitals. Conclusions: The study findings will help in scaling up the implementation of these guidelines across all district and women’s hospitals in India and lead to their effective implementation.